A comparative evaluation of contemporary models for lean manufacturing practices - Khalili, Amjad; Ismail, Md Yusof; Karim, Ahmad Izwan Mustafizul; Che Daud, Mohd Radzi (Inderscience Enterprises Ltd., 2017)
Lean manufacturing (LM) is a thought developed in Toyota, thus, there is lack of studies on whether the implementation of LM is appropriate for different enterprises because of differences in organisational and social culture and labour. This paper critically analyses 11 contemporary models for LM in an attempt to find a unified model that can be applied by enterprises. In the literature models have a tendency to focus only on few single components. However, different enterprises use diverse dimensions and models for measuring LM. It aims to review the various LM models prevailing in the contemporary research papers along with presentation of an in-depth analysis exploring the similar and dissimilar aspects. The LM models adopted by different enterprises are quite diverse as revealed through this investigation. The outcome of this study produced a matrix comprising conjoint 98 elements linked with LM 11 models. These represent soft and hard LM elements found in the literature.